2016
DOI: 10.1515/jomb-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Brain-derived Neurotrophic Factor and Nitric oxide in Patients with Schizophrenia. A pilot study/ Dijagnostička tačnost moždanog neurotrofičkog faktora i azot-monoksida kod obolelih od shizofrenije.Pilot studija

Abstract: SummaryBackgroundBrain-derived neurotrophic factor (BDNF) and nitric oxide (NO) play multiple roles in the developing and adult CNS. Since BDNF and NO metabolisms are dysregulated in schizophrenia, we measured these markers simultaneously in the blood of schizophrenics and assessed their diagnostic accuracy.MethodsThirty-eight patients with schizophrenia classified according to demographic characteristics, symptomatologyand therapy and 39 age- and gender-matched healthy controls were enrolled. BDNF was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…The meta-analysis of all studies was collected to confirm the decreasing of BDNF levels of schizophrenic patients to be compared to the control group, however, no significant results were found in no medication cases. A study conducted by Djordjevi et al, [23] in 2016 found that the BDNF serum levels were significantly lower (20.38 ± 3.73 ng/mL, P = 1.339 E-05), whereas the NO2 concentration of plasma was significantly higher (84.3 (72-121) mmol/L, P = 4.357E-08) than those who were classified as control healthy (25.65 ± 4.32 ng/mL; 60.9 (50-76) mmol/ L respectively) [23]. Based on the assessment of cognitive function for the eight domains to the schizophrenic patients, it was found positive correlation with medium power (r = 0.4 -< 0.6) to the visuospatial (r = 0.402), attention (r = 0.437), and memory (r = 0.413).…”
Section: The Correlation Of Bdnf To the Cognitive Functionsmentioning
confidence: 99%
“…The meta-analysis of all studies was collected to confirm the decreasing of BDNF levels of schizophrenic patients to be compared to the control group, however, no significant results were found in no medication cases. A study conducted by Djordjevi et al, [23] in 2016 found that the BDNF serum levels were significantly lower (20.38 ± 3.73 ng/mL, P = 1.339 E-05), whereas the NO2 concentration of plasma was significantly higher (84.3 (72-121) mmol/L, P = 4.357E-08) than those who were classified as control healthy (25.65 ± 4.32 ng/mL; 60.9 (50-76) mmol/ L respectively) [23]. Based on the assessment of cognitive function for the eight domains to the schizophrenic patients, it was found positive correlation with medium power (r = 0.4 -< 0.6) to the visuospatial (r = 0.402), attention (r = 0.437), and memory (r = 0.413).…”
Section: The Correlation Of Bdnf To the Cognitive Functionsmentioning
confidence: 99%